ANALYSIS OF SOCIAL COLLABORATION ON OVERCOMING ATTRACTIVE COMMUNITIES DURING THE COVID-19 OUTBREAK - bakar iskandar, abu; Mubarok, Zahid; Fitriah, Maria; Aprilliani, Afmi (Jurnal Sosial Humaniora, 2022)
Covid19 in 2020 caused 21,406 exposures, 16,690, 287 deaths. Due to Covid 19, many patients did not receive treatment at facilities, so they were treated independently. There are still many complaints about medical services. Medicines are too late, do not even get them. Covid19 is detrimental to social, economic, and educational life. The influence on food and beverage entrepreneurs is up to 27%, and medium entrepreneurs are 0.07%. Teaching and learning activities are carried out using the internet—the Command Center to deal with Covid-19. The Central leadership of Muhammadiyah carried out activities to raise funds to relieve the victims of COVID-19 through Aisyiyah to cope with Covid-19 Rp.78, 690,771,596. Branch Aisyiyah carried out social activities distributing food packages to employees, students, and residents. The study’s objectives were to identify the number of health facilities, record the types of medical staff, analyze drug and food aid, describe self-isolation, analyze public opinion, and provide an understanding of the social solidarity model. This research uses a qualitative descriptive design. The population is the community, and the sample is 120 people. The data used are primary and supporting. The data collection methods are dialogue, observation, documentation, and reference studies—qualitative information with content analysis and a Likert scale. The study results showed that 119 patients were treated at the Puskesmas and one at the hospital. Drug assistance for patients who have been treated in Vaccines 1 and 2. Patients treated at home were 95 people for 14 days and 13 for 15 days. Patient opinion shows 7 respondents stated very well, and 87 were quite good. The solidarity formed is of the type of organic solidarity, which is formed in modern society with a high complexity of the division of labor and important values ​​for members.